The Relationship between Corporate Social Responsibility's Disclosure and Financial Performance: An Empirical Study of Jordanian Companies Listed on Amman Stock Exchange - Abu Farha, Enas; Alkhalaileh, Mahmoud (Jordan Journal of Business Administration, 2016)
The purpose of this study is to investigate the association between the corporate social responsibility disclosure (CSRD) and the corporate financial performance, using a market-based performance measure (Stock returns) and accounting- based performance measures (ROA & ROE). The study's sample consists of 76 manufacturing companies & 59 service companies listed in Amman Stock Exchange (ASE) over the six year period (2006-2011). The empirical results reveal that the level of CSRD is relatively low with average score of 32 %. However, the CSRD score reported by this study for manufacturing companies (39%) is substantially higher than that of service companies (23%). The study's findings indicate that the level of social responsibility disclosure by manufacturing companies in Jordan has improved substantially during the last decade from CSRD score of 13% reported prior related study (Suwaidan, et al., 2004) to the 39% reported by this study. In line with most prior studies' findings, this study provides empirical evidence supports positive significant Association between CSRD and profitability measure (ROE). However, the study failed to provide empirical evidence in support of significant association between CSRD and stock returns.